A Survey on Medicine Disposal Practice among Households in Yogyakarta - Kristina, Susi Ari (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Improper disposal of unused medications has been a public health problem, as unused drug adversely effects on health and environment. The main objective of this study was to assess the extent of unused medications disposal practice of among household in Yogyakarta Province, Indonesia. Materials and Methods: A survey-based cross-sectional study was used. Households were conveniently selected and interviewed using structured questionnaires. Attitudes and practices regarding medicine disposal were asked and list of unused medicines found at home was recorded. The data were analyzed and presented descriptively. Results: Of 324 household surveyed, majority of respondents (85%) reported storing unused medications in their home and only 3% reported returning medication to a pharmacy. Antibiotics were commonly medicine kept in home (37%). Predominant reason for medication non-used was disease or symptoms felt improved (97%). Less than half of respondents (41%) have been check the expiry date of their medicine before use. Most respondents (80%) did not get any advice from health professionals. Conclusion: Gaps exist in practices of medicine disposal. An effective unused drug disposal system supported by community pharmacists should be provided along with extensive media campaign to educate customers on safe medicine disposal practices.